Deskripsi Kemampuan Menulis Matematis Siswa Kelas VIII dalam Menyelesaikan Soal Matematika - Alfi Nurulrokhimah; Supriyono Supriyono; Prasetyo Budi Darmono (Jurnal Karya Pendidikan Matematika, 2020)
This research aims to describe the mathematical writing ability students of class VIII in finishing mathematics problem. This research is a descriptive qualitative research. The sampling technique used by puposive sampling technique. The research subject were chosen by 2 students of class VIII consisting of 1 upper class student and 1 lower class student. Based on the results of data anlysis, the mathematical writing ability of upper class student fulfilling three aspect of mathematical writing ability indicators that is written texts, mathematical expressions, and drawing but it is not perfect, while lower class student only fulfilling one aspect of mathematical writing ability indicator that is drawing but not perfect. Therefore, in general the mathematical writing ability of upper class and lower class students is still not perfect because there are indicators that are less indicator fulfilled. This matter caused by misconceptions, miscalculating operations, and lack of students in understanding the material